Cooperativo de crédito solidário? A atuação da CRESOL no contexto da chamada agricultura familiar - Silva, Vosnei da (2015)
This paper aims to analyze and understand the cooperativism of the CRESOL Baser System credit, its historical development in time and space, its main characteristics, dynamics and trends, their role in agriculture and the importance for the small rural bourgeoisie. It starts with an overview of the historical cooperativism, the theoretical perspective of Marxist writers and general characteristics of the same in Brazil. Posteriorly, a characterization of brazilian agriculture, in order to understand the material structure on which develops this cooperativism credit. This understanding is essential herein because the attempted to emphasis on agricultural dynamics on the capitalist system as it is in this field and the constituents of CRESOL agriculture producers. Finally, it is emphasized the elements that we consider important of the cooperative, as internal structure, coverage areas, functions, relationships with State and financial markets, world's conception and policy, internal and external contradictions and some trends on its development. The intent, after understanding the interrelationship among this all, is to understand how to organize the known family farms agriculture in a branch of economics on the imperatives of capitalist dynamics, the chosen mechanism for this (solidarity cooperativism) and how this reflects a disruption perspective or not with this economic model.